RESPON PERTUMBUHAN BIBIT KOPI (Coffea sp.) AKIBAT PEMBERIAN KOMPOS ECENG GONDOK DAN PUPUK ORGANIK CAIR FISH WASTE - mujahidin, Mujahidin; Setiawan, Beny; Jatsiyah, Venti; Kurniawan, Tardi (Politeknik Negeri Ketapang, 2024)
The use of organic fertilizer can have a positive impact on the environment and plants so it has great potential for use in plant cultivation. This research aims to determine the interaction and appropriate dosage between the combination of water hyacinth compost and fish waste poc on the growth of coffee seedlings (Coffea sp.) in sub-soil. This research used a factorial Completely Randomized Design (CRD) consisting of 9 treatments and 3 replications. The first factor is water hyacinth compost which consists of 3 levels, namely: K0: Without water hyacinth compost K1: Water hyacinth compost with a dose of 50 g/plant K2: Water hyacinth compost with a dose of 75 g/plant. The second factor is the POC of fish waste which consists of three levels, namely: PO: No POC of fish internal organ waste P1: POC of fish internal organ waste with a concentration of 3 mL, P2: POC of fish internal organ waste with a concentration of 5 mL. Data obtained from research results were analyzed statistically using analysis of variance (ANOVA). If the data obtained has a real effect, then continue with the Duncan Multi Range Test (DMRT) at the 5% level. The research results showed that the interaction between the combination of water hyacinth compost and fish waste POC occurred on all observation parameters. The significant influence on all observation parameters of coffee seedlings was thought to be caused by the performance of the two treatment factors which supported each other. The best dose of the combination of water hyacinth compost and fish waste POC for the growth of coffee seedlings was found in treatment K2 (75g water hyacinth compost/plant) P2 (5 ml fish waste POC/plant).